ENGINEERING WEB-BASED INFORMATION SYSTEMS FOR MANAGEMENT OF WOMEN AND CHILD PROBLEM HANDLING ACTIVITIES - Zaidir Zaidir; Indra Listiawan (Institut Teknologi Dirgantara Adisutjipto, 2020)
The problem of violence against women and children, viewed from an individual as well as a social perspective, can have multiple effects. The effects such as psychological and individual health and the quality of public health. Women and children in everyday life often receive unpleasant treatment from close people and strangers. The constraints experienced are that often the two affairs are combined and handled by one sector, the number of officers is less than the cases handled, there is not enough budget to carry out follow-up actions and many residents do not want to disclose their problems directly to the authorities. There are many problems for women and children, so a